An Unexpected Small Biodiversity Oasis of Sea Slugs (Mollusca, Gastropoda, Heterobranchia) in the Largest Petrochemical Hub of Italy (Central Mediterranean) - Andrea Lombardo; Giuliana Marletta (Oceans, 2024)
The Magnisi peninsula is a small portion of land located near the largest Italian petrol-chemical pole of Augusta–Priolo–Melilli (40 km2), which, since the 1950s, devastated the local environment and landscape and unloaded directly into the sea an impressive quantity of pollutants. Unlike the terrestrial part of the area, where a Natural Oriented Reserve (NOR) called “Saline di Priolo” was established in the 2000s, no concrete legislative action has been implemented or proposed for the marine environment. At the same time, the fauna of the marine environment has not been studied in the same way as that of the terrestrial environment. As concerns the molluscan fauna, most of the information dates back to the 1800s. These studies were exclusively focused on the shells of some mollusks in the area. Instead, no study related to this area has ever been carried out on the group of sea slugs. This study conducted between 2022 and 2023, through snorkeling activities, allowed to provide the first faunistic list of the sea slugs of this area, together with information on the biology and ecology of these gastropods, highlighting the potential biodiversity present in this small stretch of coastline affected by high industrial pollution.